2010
DOI: 10.1111/j.1600-0404.2009.01275.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the antiepileptic drugs on peripheral nerve function

Abstract: Valproic acid, oxcarbazepine and topiramate don't have effects on nerve conduction studies. Mild electrophysiological changes contribute to carbamazepine therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…So far, there are no randomized controlled trials for VP, but the response to treatment with carbamazepine/oxcarbazepine supports the diagnosis [ 14 ]. Although the long-term administration of anticonvulsant drugs in epileptic patients was reported to provoke delayed auditory conduction [ 68 , 69 , 70 ], a normalization of IPL I–III was noticed in our case. Thus, it is possible that the low doses of oxcarbazepine used in VP are less toxic than the higher doses usually required in epilepsy, resulting in a beneficial effect on the narrowed IAC-induced neuropathy.…”
Section: Discussioncontrasting
confidence: 53%
“…So far, there are no randomized controlled trials for VP, but the response to treatment with carbamazepine/oxcarbazepine supports the diagnosis [ 14 ]. Although the long-term administration of anticonvulsant drugs in epileptic patients was reported to provoke delayed auditory conduction [ 68 , 69 , 70 ], a normalization of IPL I–III was noticed in our case. Thus, it is possible that the low doses of oxcarbazepine used in VP are less toxic than the higher doses usually required in epilepsy, resulting in a beneficial effect on the narrowed IAC-induced neuropathy.…”
Section: Discussioncontrasting
confidence: 53%
“…Peripheral neuropathy had been also reported with other AEDs therapy as CBZ[ 26 - 28 ], PB[ 27 ], VPA[ 26 , 29 , 30 ], GPN[ 31 ], LEV[ 32 ] and LCM[ 33 ]. A review of the literature showed that reflex sympathetic dystrophy (RSD) is precipitated by PB in 10%-30% of cases[ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kapoor et al[ 32 ] reported a case of polyneuropathy induced by LEV which improved with discontinuation of LEV. Boylu et al[ 28 ] reported mild prolongation in the distal latency of median sensory, ulnar sensory and sural nerves with diminished nerve conduction velocities with chronic CBZ therapy but not with VPA, oxcarbazepine (OXC) or TPM. Marusic et al[ 30 ] reported a 26-year-old man with weakness of flexion and abduction of the right arm and loss of sensation in the skin over the lateral upper right arm and reduced amplitude and prolonged latencies in the right axillary nerve because of a suicide attempt with VPA overdose (serum VPA level = 2896 μmol/L; therapeutic range = 350-690 μmol/L).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 There is also evidence that carbamazepine may result in a peripheral neuropathy. 7 It is uncommon for other ASMs to result in a peripheral neuropathy. Routine neurological exams testing motor function, sensory function, and gait are important to screen for this condition.…”
Section: Nervous System Effectsmentioning
confidence: 99%